The Unity of Numerical and Musical Logic - Šidiškis, Bonis (Problemos, 1982)
It is shown that numerical and musical logics, two varieties of extensive ratio logic, are common by being based on the information which people extract from the extensive ratios of stimuli. The above logics differ by domains of application, methods and goals reached.